PENGARUH LATAR BELAKANG SOSIAL DAN EKONOMI ORANG TUA TERHADAP MINAT BERWIRAUSAHA MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Nike Forestriyani; Sumarno '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study conducted at the University of Riau FKIP Economic Education with the aim to determine the effect of social and economic background of parents of student interest in entrepreneurship FKIP economy education University of Riau. The population in this study were 127 students and sampling techniques in this study using purposive random sampling by Slovin formula that results in 56 samples. Data was collected through questionnaire techniques while data types and sources of primary data and secondary data. Furthermore, the data were analyzed using multiple regression analysis, regression coefficient sececara simultaneous test (F test), partial regression coefficient test (t test), and the coefficient of determination (R2). The results showed that the variables of social and economic background of parents simultaneously affect student interest in entrepreneurship. Based on the partial test, social background variables parents in terms of parental education has a greater influence than the student interest in entrepreneurship for economic background variables in terms of parents' income level. It can be seen from the regression coefficient of 0.357373 social background variables while the economic background of 0.000003 to the value of determination coefficient of 0.455. What this means is that the contribution of the influence of the independent variable on the dependent variable is equal to 45.5%. While the remaining 54.5% is determined by other variables such as the effect of the internal factors that come from within ourselves and others that are not investigated.Keywords: Social Background Parent, Economic Background Parents' Interest In Entrepreneurship